MXenes: advances in the synthesis and application in supercapacitors and batteries - Wasnik, Kundan; Pawar, Meenakshi D.; Raphael, Leya Rose; Pullanchiyodan, Abhilash; Shelke, V. Manjusha; Raghavan, Prasanth (Journal of Materials Research, 2022)
MXenes, the newest family member of the two-dimensional materials have been widely investigated for different applications, particularly in the energy storage realm. With regard to this, MXene precursors have attained widespread attention for the application in electrochemical energy storage devices especially supercapacitors and batteries. This review has comprehensively studied various synthesis strategies adopted for MXenes including the top-down and bottom-up approaches. The shift to renewable energy alternatives have focused on the electrochemical choices such as supercapacitors and batteries, the most common and relevant ones. Thus the application of MXenes and its composite in supercapacitors as electrodes have been analyzed along with its detailed mechanism and electrochemical performance. Several battery chemistries including lithium-ion, sodium-ion and other battery systems utilizing MXenes have also been discussed here. Thus the existing strategies, advancements, and drawbacks regarding the inclusivity of MXenes in the electrochemical energy systems of supercapacitors and batteries are reviewed in this article.

Methoxyl-containing hyper-crosslinked polymer from largely bio-based biphenyl methyl ether and its application in lithium-sulfur battery - Wale, Apparav K.; Das, Anoushka K.; Patil, Nita R.; Shelke, V. Manjusha; Ambade, V. Ashootosh; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2025)
A new biphenyl methyl ether viz 2,2 `,3,3 `-tetramethoxy-5,5 `-bis(methoxymethyl)-1,1 `-biphenyl (TBMB) was synthesized starting from vanillin via three-step reaction sequence. The self-polycondensation of TBMB by employing two Bronsted acid catalysts, viz, p- toluenesulfonic acid (PTSA) and trifluoromethanesulfonic acid (TFSA) led to the formation of organic hyper-crosslinked polymers (HCPs) containing built-in methoxyl groups. HCPs were characterized by FTIR, solid state 13 C NMR, XPS, XRD, TGA, BET, and FESEM analysis techniques. HCPs synthesized using PTSA (HCP-PTSA) and TFSA (HCP-TFSA) exhibited a Brunauer-Emmett-Teller (BET) surface area of 480 +/- 5 and 590 +/- 4 m2/g, respectively and consisted of hierarchical pore structures with both micropores and mesopores. HCP-TFSA was evaluated as an active coating layer on conventional polypropylene (PP) separator in lithium-sulfur batteries to suppress the polysulfide shuttling on account of the ability of methoxyl groups to anchor soluble polysulfide species via coordination. The significant polysulfide adsorption capacity and improved cycling stability with a capacity of 617.2 mAh g- 1 at 0.5C and 99% capacity retention highlighted the potential of porous HCP containing built-in methoxyl groups in the development of attractive lithium-sulfur battery systems.
Keywords: Active coating layer; bio-based; Biphenyl methyl ether; Hyper-crosslinked polymer; lithium-sulfur battery; Methoxyl groups; Self-polycondensation